Etude de la variabilité de la forme du bec chez deux souches de poulet de chair (Cobb500 et Arbor-Acres) par la technique de morphométrie géométrique - BELAICHE, Zakaria. (My University, 2018)
This thesis allowed us to demonstrate that the geometric morphometry MG and more precisely the methodology of the reference points that we used in a 2D framework; via the Procrust overlay on digitized images of the beaks on the upper side can be widely practiced to answer our questions. MG is a truly powerful tool for visibly identifying and visualizing changes in the conformation of beaks. In this thesis using modern techniques of morphometry based essentially on the configuration of landmarks or landmarks that are part of geometric morphometry. The latter makes it possible to synthesize, on the desired scale of precision, the geometry of an object. It has an exact and rigorous mathematical foundation that guarantees robust statistics. The main objective is to study and quantify the variability of the beak forms (conformations + centroid sizes) of the two chicken strains Cobb 500 and Arbor-Acres, a total of 65 chicken (40 Cobb 500-25 Arbor-Acres). The results showed a clear differentiation. Several fields of multivariate statistical analysis were developed. The recorded shape differences mainly involve the Cobb 500 and Arbor-Acres shape parameters, while the contribution of the size of the beak (size) is generally small. Both strains have indeed significant differences in the geometry of their beaks. The large differences calculated by the generalized variances revealed the heterogeneity of the beak forms. The visualization of beak deformations clearly showed the differences in conformations. Finally, we can say that our results reveal the great interest of the MG in the study, on the one hand, we confirmed the hypothesis of the variability between the beaks of the two strains, and on the other hand, that we have encouraged to continue studying to find a radical solution to the problem to be solved
Keywords: bec; morphométrie géométrique; points-repères; superposition Procruste; conformation; forme; beak; geometric morphometrics; landmarks; Procrustes superimposition; Conformation; shape